Single‐cycle induction chemotherapy followed by chemoradiotherapy or surgery in patients with head and neck cancer: What are the best predictors of remission and prognosis?. Issue 8 (23rd December 2014) - Semrau, Sabine; Haderlein, Marlen; Schmidt, Daniela; Lell, Michael; Wolf, Walburga; Waldfahrer, Frank; Uder, Michael; Iro, Heinrich; Kuwert, Torsten; Fietkau, Rainer
<x xml:space="preserve">Abstract</x> BACKGROUND There is controversy over the concept of function and organ preservation by chemotherapy/chemoradiation instead of surgery in locally advanced cancer of the larynx or pharynx. Tumor response to induction chemotherapy (ICT) can help in choosing between conservative and surgical treatment. This study compared 3 methods of assessing response to ICT: endoscopy, computed tomography, and 18F‐FDG‐PET/CT. METHODS Primary response to 1 cycle of ICT with docetaxel plus platinum was assessed by the aforementioned methods in 62 laryngopharyngeal cancer patients. Endoscopic response was the deciding factor for selecting further treatment: surgery for endoscopic nonresponders (<30% tumor response) versus chemoradiotherapy for endoscopic responders. RESULTS ICT achieved endoscopic response in 48 of 62 patients (77%). Individual relative residual tumor activity of standardized uptake value (resSUVmax) in 18F‐FDG‐PET/CT was a median 0.38 of baseline (0.09‐1.71), whereas residual tumor extent in CT (resCT) was 0.75 of baseline (0.32‐1.20). Endoscopic responders and nonresponders differed significantly in SUVmax after ICT (postSUVmax, 6.0 vs 14.5; P < .001), resSUVmax (0.34 vs 0.81, P < .001), and resCT (0.71 vs 0.87, P = .004), but not in maximum tumor diameter after ICT (14 vs 20 mm, P = .11). resSUVmax <0.8 and absolute postSUVmax <10 provided the best discriminatory power for long‐term success criteria (tumor‐free survival, overall survival). CONCLUSIONS Metabolic tumor response showed very good correlation with clinical tumor response to ICT. The value of metabolic response detected by 18F‐FDG‐PET/CT should be explored in a prospective clinical trial. Cancer 2015;121:1214–1222. © 2014 American Cancer Society.